Peningkatan Pengetahuan Orang Tua Meningkatkan Cakupan Imunisasi DPT-HB-HiB dan MR Lanjutan pada Anak - Ni Wayan Darsani; Ni Made Dwi Purnamayanti; I Gusti Ayu Tirtawati (Midwifery Department of Health Polytechnic, Ministry of Health, Denpasar, 2023)
DPT-HB-HiB and MR immunizations are given in the basic immunization program. Re-immunization (advance immunization) is given to children aged 18 months. The purpose of advance immunization is to maintain the level of immunity and extend the child's protection period. Parental knowledge is assumed to be related to the completeness of advanced immunization in children. This study aims to determine the relationship between parental knowledge and completeness of advanced DPT-HB-HiB-MR immunization in children aged 2 years. This research is an analytic survey research with a cross sectional approach. The research was conducted in Puskesmas III Dinas Kesehatan Kecamatan Denpasar Utara in 2022. This study involved 92 parents and children aged 24-36 months. Data on parental knowledge was obtained by filling out a questionnaire. Completeness of follow-up immunizations for children is obtained from the child's immunization records. Statistical test using Chi-square. The results of this study showed that 44.6% of parents had good knowledge and 55.4% of parents had poor knowledge about advanced immunization in children. The results of this study also found 68.5% of children with complete advanced immunization status and 31.5% of incomplete advanced immunization status. There is a significant relationship between parental knowledge and the completeness of advanced immunization in children under 2 years of age at Puskesmas III Dinas Kesehatan Kecamatan Denpasar Utara (p value=0,041). Increasing parental knowledge about advanced immunization has an impact on increasing the coverage of advanced immunization in children under 2 years of age.